Analisis faktor determinan terhadap kejadian anemia pada wanita usia subur: Studi analitik - Duta Liana; Erry Yudhya; Jerry Maratis; Fifi Dwijayanti; Nuraini Fauziah (Poltekkes Kemenkes Aceh, 2026)
Background: Anemia remains a global public health problem, commonly affecting women of reproductive age, with a prevalence of approximately 30% worldwide and 32% in Indonesia. This condition is influenced by multifactorial determinants, including nutritional status, iron levels, reproductive factors, and education and knowledge levels.Objectives: This study aimed to identify the main determinants of anemia in women of reproductive age.Methods: This quantitative study used an analytical observational design with a cross-sectional approach. Data were gathered through interviews and anthropometric measurements of 44 women of reproductive age (15–49 years) from Cikeas Udik Village, Bogor Regency. Bivariate analysis was conducted using the chi-square test, and multivariate analysis was conducted using logistic regression analysis.Results: Nutritional status was significantly associated with anemia (p = 0.033). Respondents with abnormal nutritional status had a nine-fold higher risk of developing anemia than those with normal nutritional status (OR = 9.391; 95% CI: 1.205–73.178). Although iron supplementation in the past year did not show a statistically significant association with anemia (p = 0.108), it tended to reduce the risk of anemia. Conclusion: Nutritional status is a significant determinant of anemia in women of reproductive age. These findings highlight the importance of improving nutritional status through balanced nutrition education, adequate micronutrient intake, and adherence to iron supplementation.